PENILE HEMODYNAMIC RESPONSE TO PHOSPHODIESTERASE TYPE V INHIBITORS AFTER CAVERNOSAL SPARING INFLATABLE PENILE PROSTHESIS IMPLANTATION A PROSPECTIVE IMPLANTATION: A PROSPECTIVE RANDOMIZED OPEN-BLINDED END-POINT (PROBE) STUDY - ALI , J; BANGASH , MH; HAMZA , M; SHAHID , M; TARIQ , F; HAMMAD , M; ASIM , F (Biological and Clinical Sciences Research Journal, 2024)
Oral phosphodiesterase type V inhibitors (PDE5i), such as sildenafil (Viagra), tadalafil (Cialis), and vardenafil (Levitra), have become the first-line pharmacological treatment for most cases of ED. Objective: The main objective of the study is to find the penile hemodynamic response to phosphodiesterase type v inhibitors after cavernosal-sparing inflatable penile prosthesis implantation prospective implantation. Objective: To evaluate the penile hemodynamic response, erectile function, and patient satisfaction associated with PDE5i therapy after cavernosal sparing IPP implantation. Methods: This Prospective Randomized Open-Blinded End-Point (PROBE) was conducted at Mardan Medical Complex Peshawar from June 2024 to December 2024. Data were collected from 25 male patients. Patients underwent cavernosal sparing IPP implantation and were randomly assigned to two groups: Group A (n=13) received PDE5i postoperatively, while Group B (n=12) received a placebo. Hemodynamic measurements using Doppler ultrasound were conducted at baseline, 6 weeks post-surgery, and the 6-month follow-up. International Index of Erectile Function (IIEF) scores and patient satisfaction were also assessed. Results: Group A showed significant improvements in penile hemodynamics compared to Group B, with a higher peak systolic velocity (PSV: 38.7 ± 6.1 cm/s vs. 24.5 ± 5.3 cm/s), reduced end-diastolic velocity (EDV: 4.8 ± 2.3 cm/s vs. 8.9 ± 2.4 cm/s), and improved resistance index (RI: 0.88 ± 0.07 vs. 0.64 ± 0.09) at 6 months. Group A also reported higher IIEF scores and greater satisfaction with sexual function. Conclusions: Cavernosal sparing IPP implantation combined with PDE5i therapy significantly improves penile hemodynamics, erectile function, and patient satisfaction compared to IPP alone. This dual approach offers enhanced outcomes for managing severe ED.